Pengaruh Ukuran Perusahaan dan Financial Distress terhadap Integritas Laporan Keuangan: Studi Empiris pada Perusahaan Pertambangan BEI Tahun 2018-2022 - Piliang, Alif Aulia; Afriyenti, Mayar (Jurnal Nuansa Karya Akuntansi, 2024)
This research aims to find out the effect of company size and financial distress on the integrity of financial statements in listed mining companies on the Indonesia Stock Exchange during the period from 2018 to 2022. This research is quantitative in nature. The sample collected consisted of 70 data points, selected using a purposive sampling technique. Secondary data for this study was obtained from www.idx.co.id or the respective company websites. The data was analyzed using multiple linear regression analysis. Based on the results of hypothesis testing, it was found that company size has no significant effect on the integrity of financial statements. On the other hand, financial distress was found to have a significant positive effect on the integrity of financial statements. This indicates that as financial distress increases, the integrity of financial statements also improves, possibly due to stricter scrutiny and regulatory compliance during periods of financial difficulty. The findings contribute to the understanding of factors influencing financial statement integrity in the mining sector.